Peningkatan Motivasi Belajar Ipa Melalui Penerapan Model Pembelajaran Teams Games Tournament (Tgt) Pada Siswa Kelas IV SD Negeri Karangasem IV Surakarta Tahun Ajaran 2015/2016 - TRISNANI, ARVINA WAHYU, Dr. Achmad Fathoni, S.E., M.Pd (2016)
PENINGKATAN MOTIVASI BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) PADA SISWA KELAS IV SD NEGERI KARANGASEM IV SURAKARTA TAHUN AJARAN 2015/2016 Universitas Muhammadiyah Surakarta arvinawahyu@gmail.com ABSTRACT The purpose of this research is: 1) to increase students motivation in science, 2) to increase students achievement on science. The kind of this research is Classroom Action Research (PTK). The study was conducted during two cycles or four meetings. The subject of this research is teacher dan 34 students. Data collection techniques are: observation, test, documentation and interviews. The validity of the data using a triangulation of data sources, triangulation methods and validity. The process of data analysis include: data collection, data reduction, data display and conclusion. The results of the study, showed the improvements students motivation and students achievements in science. These results show that indicators of students motivation improve which include: 1) diligent on the task, 41.18% (pre-cycle), 60.29% (cycle I), 88.23% (Cycle II); 2) resilient difficulties, 38.24% (pre-cycle), 61.76% (Cycle I), 89.70% (Cycle II); 3) happy to solve the problem of task, 38.24% (pre-cycle), 61.76% (Cycle I), 83.82% (Cycle II); 4) attention to the teacher explanations, 38.24% (pre-cycle), 67.65% (Cycle I), 95.59% (Cycle II); 5) have the desire succeed, 44.12% (pre-cycle), 66.18% (Cycle I), 92.65% (Cycle II); 6) creating a conducive learning environment 44.12% (pre-cycle), 60.29% (Cycle I), 86.76% (Cycle II). Students achievements incrased from 44.12% (pre-cycle), 61.76% (first cycle), and 91.18% (second cycle). The conclusion of this study is the implementation of Teams Games Tournament (TGT) learning model can increase the science students motivation and students achievements in 4th grade students of SD Negeri Karangasem IV Surakarta year 2015/2016. Keywords: learning model, student achievement, student motivation, Teams Games Tournament (TGT)